Anxiety symptoms as a moderator of the reciprocal links between forms of aggression and peer victimization in middle childhood. Issue 5 (20th February 2017) - Cooley, John L.; Frazer, Andrew L.; Fite, Paula J.; Brown, Shaquanna; DiPierro, Moneika
Abstract : The current short‐term longitudinal study evaluated whether anxiety symptoms moderated the bidirectional associations between forms (i.e., physical and relational) of aggression and peer victimization over a 1‐year period during middle childhood. Participants were 228 predominantly Caucasian children (50.4% boys; M  = 8.32 years, SD = .95 years) in the second through fourth grades and their homeroom teachers. Children completed a self‐report measure of anxiety symptoms at Time 1. Peer victimization was assessed using self‐reports at Time 1 and approximately 1 year later (Time 2), and teachers provided ratings of children's aggressive behavior at both time points. A series of cross‐lagged path analysis models indicated that high (+1 SD) initial levels of anxiety symptoms exacerbated the prospective link from Time 1 relational aggression to Time 2 peer victimization; conversely, when initial levels of anxiety symptoms were low (−1 SD), relational aggression predicted lower levels of subsequent peer victimization. Time 1 peer victimization was also found to predict lower levels of Time 2 physical aggression when initial levels of anxiety symptoms were low, and Time 1 anxiety symptoms were uniquely related to higher levels of relational aggression over a 1‐year period. Regions of significance were calculated to further decompose significant interactions, which did not differ according to gender. Study findings are discussed within a social information processing theoretical framework, and directions for future research and implications for practice are reviewed. Specifically, co‐occurring anxiety symptoms may need to be addressed in interventions for both aggression and peer victimization during middle childhood.